2005
DOI: 10.1080/08035250510025987
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and educational outcomes in early adulthood for infants weighing 1000 grams or less at birth

Abstract: ELBW subjects had a mean adult IQ in the normal range; however, it was one standard deviation below that of NBW subjects and they had more school failures. Despite this, more than half of ELBW subjects aged 18 y or more had obtained their secondary school diploma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 21 publications
(21 reference statements)
0
24
0
1
Order By: Relevance
“…[8][9][10] We accepted 10 and 15% as reasonable responses. Therefore, 50% of the answers were considered acceptable).…”
Section: Cp Prevalencementioning
confidence: 92%
“…[8][9][10] We accepted 10 and 15% as reasonable responses. Therefore, 50% of the answers were considered acceptable).…”
Section: Cp Prevalencementioning
confidence: 92%
“…33 The population-linkage studies have reported rates of CP in term adults of 0.19% in Denmark 6 and 0.13% in Norway. 4 Rates of other sensory impairments are higher in EP subjects than in controls and are generally higher in ELBW cohorts than in VLBW cohorts; bilateral blindness ranged from 7.4% in an ELBW cohort 33 33,34 although in 1 study there was 1 case of deafness of 233 controls (0.4%). 35 In addition to blindness, more survivors of extreme prematurity require prescription glasses than do controls (64% vs 37% in 1 study 29 ).…”
Section: Neurosensory Impairmentsmentioning
confidence: 98%
“…32 Reported rates of CP in adulthood are consistent with these observations and are a little higher in cohorts of those who were either of Ͻ1001 g birth weight or Ͻ28 or Ͻ29 weeks' gestation (13.4% 33 or 7.2% 34 in ELBW cohorts, 9.1% at 23-27 weeks' gestation, 4 or 8.7% at either Ͻ29 weeks' gestation or Ͻ1001 g birth weight 23 ) compared with rates in VLBW cohorts (6.9%, 5 6.6%, 35 4.7%, 36 or 8.5% 37 on self-report), or 4.1% in those born at Ͻ33 weeks' gestation in a population-linkage study. 6 Rates of CP in controls are typically low and mostly zero in cohort studies with concurrent controls, 23,34,35,37 because the sample sizes are relatively small compared with the expected frequency of Ͻ1 in 500. 32 There was, however, 1 case of CP in 133 (0.8%) controls in 1 study.…”
Section: Neurosensory Impairmentsmentioning
confidence: 99%
“…These deficits are evident by school entry, persist throughout the school-age years, and are costly to treat (Chaikind and Corman, 1991;Saigal et al, 2000;Pharoah et al, 2003;Roth et al, 2004;Lefebvre et al, 2005). Many survivors have relatively selective impairments in academic skills, possibly related to specific neuropsychological weaknesses (Litt et al, 2005).…”
mentioning
confidence: 99%